Accumulation and effects of dietary advanced glycation end products on the gastrointestinal tract in rats. (17th May 2018) - Yuan, Xiaojin; Zhao, Jinsong; Qu, Wanting; Zhang, Yingxiao; Jia, Benpan; Fan, Zhiyi; He, Qihan; Li, Juxiu
Summary: The gastrointestinal (GI) tract represents the first barrier against the penetration of organisms by dietary advanced glycation end products (AGEs), but the tissue accumulation of AGEs and AGE‐induced effects on the GI tract have yet to be completely elucidated. This study aimed to investigate the tissue accumulation of AGEs and AGE‐induced oxidative stress and inflammation in the GI tract of rats after long‐term consumption of AGEs from bread crust (BC). The GI tract was then removed to analyse carboxymethyllysine (CML) and malondialdehyde (MDA) contents, the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH‐Px) and the levels of tumour necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6). This study demonstrates that the oral intake of AGEs promotes their accumulation in the GI tract, and AGEs attenuate the first‐line antioxidant defence and stimulate the inflammatory response of the GI tract by downregulating enzymatic antioxidative pathways and increasing inflammatory cytokine levels. Abstract : Rats were fed a diet containing commonly consumed AGEs obtained from bread crust to investigate the tissue accumulation of AGEs, AGE‐induced oxidative stress and inflammation in the GI tract of rats. The oral intake of AGEs promotes their accumulation in the GI tract. Additionally, AGEs attenuate the first‐line antioxidant defence and stimulate the inflammatory response of the GI tract by downregulating enzymatic antioxidative pathways and increasing inflammatory cytokine levels.